Relevant Learning Media to Improve Mathematics Learning Outcomes Algebraic Topics and Pythagorean Theorems: A Literature Study - Meilina, Dika Dwi; Hidayati, Diah Nur; Jailani, Jailani; Setyaningrum, Wahyu (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Mathematics learning media is a tool that is used to convey mathematics material so as to make abstract material more concrete and easily understood by students. This article aims to find out the suitable learning media applied to the mathematics subject of Algebra and the Pythagorean theorem. This research method uses descriptive qualitative research with a literature study approach to analyze various literature sources related to mathematics learning media. Based on the results of searches that have been conducted by the author through scopus, scient direct, sinta 1 and 2 in 2020 to 2024, 10 articles are obtained that are suitable for learning media for Algebra and the Pythagorean theorem. The results showed that non-digital based learning media is very minimal in application. While learning media that are currently widely used are digital-based learning media. Digital-based learning is used by utilizing android and website. In utilizing android, there are several that are used, namely Edmodo, Algebra Adventure Media, and OBAR. On the utilization of the website there are also several that are used, namely Google Sites, Multimedia Learning, Macromedia Flash 8, Articulate Storyline, Adobe Animate CC (OPERAL), and Almath Game